Pengaruh Harga Cryptocurrency dan Komoditas Terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2020-2024 - Azka Fadhilah; Rina Susanti (Teewan Journal Solutions, 2026)
This study aims to investigate the impact of cryptocurrency and commodity prices on the movement of the Composite Stock Price Index (IHSG) in Indonesia during the period 2020–2024. Motivated by the increasing complexity and interconnectivity of global financial markets, this study examines the independent variables of Bitcoin, Ethereum, gold, and world crude oil prices against the dependent variable of the IHSG, based on the Efficient Market Hypothesis (EMH). Using a quantitative approach, this study analyses monthly secondary data through a multiple linear regression model. The results of the analysis show that, simultaneously, the four independent variables have a significant effect on the IHSG. However, partial testing produced different findings: only the prices of gold and global crude oil were found to have a significant effect, while the prices of Bitcoin and Ethereum did not show a statistically significant effect. Furthermore, the coefficient of determination (Adjusted R Square) value of 0.874 indicates that 87.4% of the variation in the IHSG can be explained collectively by the four predictor variables in this model.